2022
DOI: 10.1177/00333549221083740
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for COVID-19 Positivity and Hospital Admission Among Arab American Adults in Southern California

Abstract: Objective: Little is known about risk factors associated with COVID-19 infection among Arab American people. We aimed to understand the predictors of receiving a positive COVID-19 test result and being admitted to the hospital for COVID-19 among Arab American adults using data from a hospital near an Arab ethnic enclave. Methods: We used electronic medical record data for Arab American adults aged ≥18 years from March 1, 2020, through January 31, 2021, at Sharp Grossmont Hospital in La Mesa, California. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…It is important to better understand the links between different risk factors and the behaviors that drive them so targeted responses and interventions can be designed. This relationship between risk factors was also observed in the most commonly reported risk factors, minority ethnicity or race and country of birth ( 18 , 28 , 30 , 31 , 36 , 37 , 41 , 43 , 46 ). As previously highlighted, one study found that speaking a language other than English in the household, was an indicator of increased risk of infection ( 41 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is important to better understand the links between different risk factors and the behaviors that drive them so targeted responses and interventions can be designed. This relationship between risk factors was also observed in the most commonly reported risk factors, minority ethnicity or race and country of birth ( 18 , 28 , 30 , 31 , 36 , 37 , 41 , 43 , 46 ). As previously highlighted, one study found that speaking a language other than English in the household, was an indicator of increased risk of infection ( 41 ).…”
Section: Discussionsupporting
confidence: 58%
“…The ethnic minority groups which were reviewed varied considerably between studies, due to the different regions each study was conducted in. Studies from the USA commonly explored Hawaiian/Pacific Island, Hispanic or Latinx communities ( 30 , 31 , 36 , 37 , 41 , 43 ) where conversely, studies conducted through Europe, would investigate other European nations or African regions ( 21 , 28 , 46 ). One study also reviewed the use of non-English language in the family/home and found that the use of non-English language increased infection risk ( 41 ).…”
Section: Resultsmentioning
confidence: 99%